1993
DOI: 10.1016/s0022-5347(17)36088-3
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Penile Incarceration by the String Method: 2 Case Reports

Abstract: We report 2 cases of penile incarceration in a 10-year-old boy and a 40-year-old man. In both cases the penis was encircled by a metallic object. The string method described was successful, rapid, atraumatic and simple to use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 7 publications
0
33
0
2
Order By: Relevance
“…The purported motives for placement of constricting objects are almost always sexual in nature in adult population [2,3,5,7,14,15,16,17]. All the 3 patients in this series placed these metallic objects for sexual gratification.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The purported motives for placement of constricting objects are almost always sexual in nature in adult population [2,3,5,7,14,15,16,17]. All the 3 patients in this series placed these metallic objects for sexual gratification.…”
Section: Discussionmentioning
confidence: 94%
“…All the 3 patients in this series placed these metallic objects for sexual gratification. Few of the published reports have analyzed the psychiatric status of these patients [7,14,16] and it is likely that a more detailed evaluation of cognitive state of these patients by trained psychologists may reveal underlying contributory factors. All the 3 patients in our series were assessed by a psychiatrist and one patient having severe depression was put on appropriate therapy while another patient was advised regular counseling sessions for psychological erectile dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vahasarja et al [7] reported two cases successfully managed by this method. Detweiler and Perkins [8] used latex band in a similar fashion calling it the Wrapping Technique.…”
Section: Discussionmentioning
confidence: 99%
“…Elle peut aussi etre associee une aspiration du sang par le gland ( Figure 3) [6]. Cette technique donne de bons resultats pour les grades I, II et III, permettant une decompression sans lesions des tissus [5,12,19].…”
Section: La M~thode Du Filunclassified